Influence of the gut microbiome on appetite-regulating neuropeptides in the hypothalamus: Insight from conventional, antibiotic-treated, and germ-free mouse models of anorexia nervosa - Roubalová, Radka; Procházková, Petra; Kovářová, Tereza; Ježková, Janet; Hrnčíř, Tomáš; Tlaskalová-Hogenová, Helena; Papežová, Hana (Neurobiology of disease, 2024)
Recent research highlights the profound impact of the gut microbiome on neuropsychiatric disorders, shedding light on its potential role in shaping human behavior. In this study, we investigate the role of the gut microbiome in appetite regulation using activity-based anorexia (ABA) mouse model of anorexia nervosa (AN) - a severe eating disorder with significant health consequences. ABA was induced in conventional, antibiotic-treated, and germ-free mice. Our results show the clear influence of the gut microbiome on the expression of four orexigenic (neuropeptide Y, agouti-related peptide, melanin-concentrating hormone, and orexin) and four anorexigenic peptides (cocaine- and amphetamine-regulated transcript, corticotropin-releasing hormone, thyrotropin-releasing hormone, and pro-opiomelanocortin) in the hypothalamus. Additionally, we assessed alterations in gut barrier permeability. While variations were noted in germ-free mice based on feeding and activity, they were not directly attributable to the gut microbiome. This research emphasizes that the gut microbiome is a pivotal factor in AN's appetite regulation beyond just dietary habits or physical activity.
Keywords: myši; Animals; Gut barrier; mentální anorexie; střevní mikroflóra; Humans; Activity-based anorexia model; hypothalamus; neuropeptidy; Appetite; Microbiome; lidé; Mice; zvířata; Neuropeptides; Neuropeptide Y; Appetite regulation; Hypothalamus; Gastrointestinal Microbiome; Anorexia Nervosa; chuť k jídlu; Eating disorders